High-modulus and strength carbon nanotube fibers using molecular cross-linking - Park, Ok-Kyung; Choi, Hoikil; Jeong, Hanbin; Jung, Yeonsu; Yu, Jaesang; Lee, Jae Kwan; Hwang, Jun Yeon; Kim, Seung Min; Jeong, Youngjin; Park, Chong Rae; Endo, Morinobu; Ku, Bon-Cheol (Pergamon Press Ltd., 2017)
We present a systematic and simple approach to produce high-strength carbon nanotube fibers (CNTFs) with electrical conductivity in the high performance range (> 1000 S/cm). We studied several critical parameters to improve the mechanical properties of CNTFs by aryl cross-linking reaction. Both the molecular dynamics (MD) simulations and experimental results showed that the mechanical properties strongly depended on the degree of cross-linking, length of cross-linkers, and CNT diameter. The monobenzene (MB) covalent bonding between CNTF with double-walled CNTs (DWCNTs) showed the highest load transfer, resulting in significantly enhanced specific tensile strength (3.7 N/tex) and Young's modulus (210 N/tex) which are superior to the strongest commercial carbon fiber (3.6 N/tex and 180 N/tex), respectively. Furthermore, the mechanical properties of aryl cross-linked CNTF exhibited no significant change in strength with sample size of CNTFs, showing uniformity of strength with increasing degree of cross-linking. The electrical conductivity of the MB cross-linked CNTFs was similar to 1400 S/cm, which is higher than the best value of commercial carbon fibers (715 S/cm). These results demonstrate that aromatic linker between CNTFs can significantly enhance mechanical properties without significant loss of electrical conductivity. These molecular engineering with MD simulations provide an important route to design and develop ultra-high-performance fibers. (C) 2017 Elsevier Ltd. All rights reserved.